The influence of warm-up on reaction time in elite football players - Juras, G.; Gruszka, P.; Szyngiera, W. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
The effect of warming up on sport performance has been studied extensively for many years. It is well known that warm-ups provide benefits for metabolic processes and help to avoid injury. One of the most important facts is that after a proper warm-up, the nervous system is activated. This is caused by increased temperature and improved nerve impulse transmission (Astrand et al, 2000). Despite many studies this phenomena has not been fully examined. It seems that the volume and intensity of a warmup can influence sport performance in many ways. The purpose of this study was to investigate the role of warm-up on reaction time in elite football players. Methods The research was conducted on nineteen (n=19) skilled football players aged from 19 to 23 years. All subjects gave informed consent for their participation in the experiment and were naive as to the purpose of the research. Three different warm-up procedures were performed and a measurement of reaction time was done three times during consecutive training sessions. The second and third measurements were provided after 3 days of rest with no control game during that period. The experimental conditions were consistent during all days of the experiments. Reaction time was measured by computer programme (with accuracy of 0.001 s). Players were examined in the preparation period of season. The significance of differences in time reaction between the three warmup types was calculated with the use of ANOVA, while differences in particular groups were calculated by Tukey`s Post-hoc tests. Results Results of this study have shown statistically significant effects for a type of warm-up on reaction time (F=4.19, p<0.01). Post-hoc analysis showed statistical significance between the second and third type of warm-up (p<0.001). The empirical data indicates that the reaction time does not depend on volume of warm-up, but on its intensity. The most important is to include anaerobic exercises to increase performance. The findings have implications for sport training.